Indigenous Knowledge of Dayaks Bakumpai in Barito Kuala District on the Management of Plant Diversity Growing at Streams and Swamps - Darmono Darmono; AHMAD SOFYAN; WAHYU WAHYU; HERITA WARNI (Journal of Wetlands Environmental Management, 2013)
Research aimed at describing profile of indigenous knowldge owned by the Dayaks Bakumpai in Batola district on managing the diversity of herbs growing at the river flow and swamp. Data on herb used by the tribe were grouped based on the etnobotanic study, covering study botany, etnofarmacology, etnoantrophology, etnolinguistik and etnoekologi. We also observed how the Dayaks Bakumpai in Batola district preserve the diversity of plant in around them, and how their efforts in bequeathing or teaching the traditional knowledge of an old breed generation to his young daam in managing diversity of herbs around them.Â  The study was carried out at three vellages, namely Simpang Arja, Pengulu and Ulu Benteng. The results showed that 52 plant species living along the river and 67 species that live in the marsh. Based on the interview we found that (1) the profile of indigenous knowldge dayaks bakumpai district batola in making use of the diversity of plant in surrounding shown through etno-linguistic, etno-economy, etno-anthropology, etno-farmacology and etno-ecology against 44 tufted herbs of 67 of herbs found, (2) Dayaks Bakumpai in Batola district, to preserve the diversity of plant surrounding them, have done without planting, but by making use of herbs without a certain rule, making use of herbs by a certain rule, making use of herbs let plant grown in nature, and destroy plants that exist or cultivated, and (3) efforts for the inheriting the indigenous knowldge to its young generation have been done by women and quite alarming that many young ages of Dayaks Bakumpai do not know the name of herbs around them.